Army spouses : military families during the Global War on Terror - Ender, Morten G., 1960- (University of Virginia Press, 2023)
"This book is about military family separations during the Global War on Terror, told through the voices of spouses married to US Army soldiers reflecting on stages of the deployment cycle, including experiences of children and experiences with social supports, social, and mass media"--